Ab initio quantum chemical studies of isotopic fractionation during acid digestion reaction of dolomite for clumped isotope application. (15th September 2020) - Pramanik, Chirantan; Ghosh, Prosenjit; Banerjee, Sanchita; Liang, Mao‐Chang
Abstract : Rationale: In 'clumped isotope paleothermometry' carbonates are reacted with anhydrous phosphoric acid to extract CO2 that carries the isotopic signature of the reacting carbonates, and the amount of clumping in the product CO2 is measured. Previous theoretical models for determining clumped isotopic fractionation in product CO2 during acid digestion of carbonates are independent of the cations present in the carbonate lattice. Hence further study is required to understand the cationic effect. Methods: We studied the acid reaction mechanism based on the protonation of carbonates, calculated the acid fractionation factor for dolomite using the partition functions and vibrational frequencies obtained for the transition state structure, and determined the effect of cations on the acid fractionation factor. Experimentally, carbonates are reacted using the modified sealed vessel method and analyzed in the dual inlet of a ThermoFinnigan MAT 253 isotope ratio mass spectrometer. Results: The oretically obtained acid fractionation factor can be expressed as Δ47 acid fractionation in dolomite = −0.28563 + 0.49508 * (10 5 /T 2 ) − 0.08231 * (10 5 /T 2 ) 2 for a temperature range between 278.15 and 383.15 K. The theoretical slope of the dolomite–acid digestion curve is lower than that of the calcite–acid digestion curve obtained using the identical reaction mechanism. Our theoretical slope is consistent with the result from the common acid bath experiments but higher than the slope obtained in our experimental study using the modified sealed vessel method and in a previous theoretical study using the H2 CO3 model. Conclusions: The transition state structure, obtained in our study, includes the cations present in the carbonate minerals and provides distinct acid fractionation factors for calcite and dolomite. The observed gentler slope of the theoretically calculated dolomite–acid digestion curve than of the calcite curve is expected considering the stronger Mg–O bond. Our experimental approach invokes post‐digestion isotopic exchange and agrees with the previous theoretical estimates where post‐digestion isotopic fractionation was considered.